Wind-induced damage in two regions of Argentina - Natalini, Bruno (2012)
Information on wind-induced damage to civil structures in Argentina is scarce. In this paper, general trends regarding both meteorological conditions and patterns of damage when damage occurred in two regions of Argentina are presented. The regions under study were the north-east of Argentina (NEA) and the north-Patagonia. This research is based on a collection of data comprising field surveys conducted after the passage of destructive storms, NCEP/NCAR Reanalysis, a Global Data Assimilation System model and other secondary sources like emergency services, local press, local councils and the National Weather Service. It is shown that both regions have similar problems of vulnerability, even though they have different meteorological environments. Topics that must be addressed to reduce the vulnerability of civil structures have been identified.